Exploring relationship satisfaction in mothers of children with disabilities: the predictive role of interparental conflicts and moderating role of dyadic coping - Vrankić Pavon, Marijana; Wagner Jakab, Ana; Löw, Ajana (Frontiers in Psychiatry, 2024)
Background Parenting responsibilities, while a source of happiness, often lead to considerable stress for parents of children with disabilities. While most parents try to cope with these challenges together, some level of interparental conflict is almost inevitable. Frequently assuming primary responsibility for children with disabilities, mothers can be substantially impacted by interparental conflict with their partners and the resulting stress. However, implementing dyadic coping strategies in managing stressful situations serves as a buffer against adverse effects, while also enhancing relationship satisfaction. Objective This study aimed to explore the relationship between interparental conflicts, dyadic coping, and relationship satisfaction among 232 mothers of children with disabilities in Croatia who were in an intimate relationship and shared a household with their partners, regardless of marital status. Methods We analysed a non-probabilistic sample of women in Croatia who reported being in an intimate relationship, sharing a household with a partner (whether married or simply cohabitating) and being a mother to a child with a diagnosed developmental disability. Participants completed questionnaires online in March of 2021 (sociodemographic variables, the Parent Problem Checklist, the Dyadic Coping Inventory and the Marriage Quality Index). Results Results of hierarchical multiple regression show that mothers’ perceptions of how they help their partner cope with stress do not predict how satisfied they are in a relationship; instead, relationship satisfaction depends on their perceptions of how their partner helps them and how they cope with stress as a team. Furthermore, moderation analysis revealed the effect of interparental conflicts were entirely mitigated by high supportive and low negative dyadic coping of the partner. When mothers felt adequately supported by their partner, the negative impact of stress caused by interparental conflicts did not spill over into their relationship. Conclusion Our results suggest that by recognizing the importance of psychological support and couples therapy in strengthening dyadic coping, government and non-profit initiatives can effectively empower parents of children with disabilities, fostering healthier and more resilient family dynamics that promotes the well-being of parents and their children.